The Role of Online Customer Reviews and Online Customer Ratings on Purchasing Decisions on E-Commerce Shopee - Rizki Amelia Iskandar; Hepiana Patmarina (International Journal of Economics, Business and Innovation Research, 2024)
This research aims to investigate how online customer reviews and ratings influence purchasing behavior on the Shopee e-commerce platform. Utilizing online survey methods, data were collected from students at the University of Bandar Lampung who are active Shopee users to understand the relationship between online customer reviews and ratings with purchasing decisions. Multiple linear regression analysis was employed to test the influence of independent variables on the dependent variable. Findings indicate that both factors significantly impact purchasing decisions on Shopee. The implications of these results highlight the importance of managing and improving the quality of customer reviews and ratings to create a positive shopping experience and motivate more purchasing decisions on e-commerce platforms. This research provides valuable insights for e-commerce practitioners to optimize their marketing strategies and brand reputation management on platforms like Shopee. By understanding the crucial role of customer reviews and ratings, companies can develop more effective strategies to enhance consumer trust and drive sales growth. Furthermore, this research contributes theoretically by expanding understanding of the factors influencing purchasing decisions in the context of e-commerce.